Using statewide administrative data and brief mental health screening to estimate the prevalence of mental illness among probationers. (June 2019) - Van Deinse, Tonya B.; Cuddeback, Gary S.; Wilson, Amy Blank; Lambert, Michael; Edwards, Daniel
There is little published information about the measures that probation agencies in the United States use to identify individuals with mental illnesses who are under community supervision. This study used statewide administrative data to estimate and compare the prevalence of mental illnesses among probationers using officer report and offender self-report data. Prevalence estimates of mental illnesses ranged from 15 percent to 19 percent, which is consistent with prior studies that used formal diagnostic assessments. In the absence of costly and time-consuming diagnostic assessments, probation agency-developed mental health scales can aid in identifying those who might be in need of additional mental health assessment.